2012
DOI: 10.1002/cmmi.491
|View full text |Cite
|
Sign up to set email alerts
|

Development of 177Lu‐nanobodies for radioimmunotherapy of HER2‐positive breast cancer: evaluation of different bifunctional chelators

Abstract: Nanobodies show favourable pharmacokinetic characteristics for tumor targeting, including high tumor-to-background-ratios. Labelled with a therapeutic radionuclide, nanobodies could be used as an adjuvant treatment option for HER2-overexpressing minimal residual disease. The therapeutic radionuclide Lutetium-177 is linked to the nanobody using a bifunctional chelator. The choice of the bifunctional chelator could affect the in vivo behaviour of the radiolabeled nanobody. Consequently, we compared four differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 22 publications
5
87
0
1
Order By: Relevance
“…With regard to the effect of radionuclide and labeling method on these parameters, we note that in a previous study with 5F7 (with a cys-tag) labeled using [ 125 I]SGMIB, intracellular retention in this cell line was maintained at about 60 % for up to 24 h as was the case with another residualizing radioiodination agent [36]. The 2Rs15d sdAb has been radiolabeled with several radionuclides including F-18 [18], Ga-68 [24], Tc-99m [23], and Lu-177 [38, 39]; however, these publications did not include internalization experiments for comparison to the current study.…”
Section: Discussionmentioning
confidence: 93%
“…With regard to the effect of radionuclide and labeling method on these parameters, we note that in a previous study with 5F7 (with a cys-tag) labeled using [ 125 I]SGMIB, intracellular retention in this cell line was maintained at about 60 % for up to 24 h as was the case with another residualizing radioiodination agent [36]. The 2Rs15d sdAb has been radiolabeled with several radionuclides including F-18 [18], Ga-68 [24], Tc-99m [23], and Lu-177 [38, 39]; however, these publications did not include internalization experiments for comparison to the current study.…”
Section: Discussionmentioning
confidence: 93%
“…The observation that the removal of the His 6 results in much lower kidney retention could be explained by differences in the overall charge of the Nanobodies because the pH in the kidney is below the pK a (negative logarithm of the acid ionization constant) of the imidazol groups. Presumably, other factors besides charge effects also are involved in the mechanism of kidney retention, and it is important to address this issue especially with regard to therapeutic applications of Nanobodies radiolabeled with b 2 -emitting radionuclides (28).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the characterisation of 68 Ga-labeled 2Rs15d was also described in terms of clinical immuno-PET imaging 16. Finally, the His-tagged anti-HER2 2Rs15d was also radiolabeled with 177Lu and biodistribution was assessed in xenografted mice 20. In the latter study we demonstrated that the bifunctional chelator 1B4M-DTPA was the preferred chelator for 177 Lu-labeling as it exhibited the most favorable biodistribution.…”
Section: Introductionmentioning
confidence: 89%